A permissive approach for optimization of L-glutaminase production using wheat bran as supporting substrate and assessment of its cytotoxic potentialities - Soren, Jyoti P.; Halder, Suman K.; Mondal, Joy; Hor, Papan K.; Mohapatra, Pradeep K. D.; Mondal, Keshab C. (Acta Biologica Szegediensis, 2020)
Microbial L-glutaminase has considered as one of the most important therapeutic enzymes considering its anticancer or antitumor activity. In this study, one L-glutaminase producing potent fungus was isolated from the coastal soil and identified as Fusarium nelsonii KPJ-2. During parametric optimization, it was noted that wheat bran supported maximum L-glutaminase production than other agro-industrial wastes tested. Solid substrate fermentation was mechanized with optimum pH of 4.0, incubation temperature at 25 °C, inoculums concentration of 2.0% (v/v), substrate concentration of 7.0% (w/v) and moisture of the production media suits at 20.0% (w/v). Statistical optimization using Response Surface Methodology (RSM) was improved the L-glutaminase production by 14.5% (68.93 U/gds) than unoptimized state. The SEM-EDX analysis demonstrated the overgrowth of fungus on wheat bran and utilization of its associated minerals. A comparative cytotoxic effect of the partial purified glutaminase was examined on both cancerous HCT cell and normal Vero cell line. The result clearly demonstrated that L-glutaminase from F. nelsonii KPJ-2 is specifically cytotoxic against cancer cell line with IC50 of 203.95µg/ml, but, non-responsive against normal cell. The newly isolated fungal strain can produce a considerable amount of L-glutaminase utilizing very low-cost substrate and the enzyme have therapeutic value for real life application owing to its anticancer effectiveness.